Analysis of Compatibility Between Curriculum 2013 and the Concept of Islamic Education - Zainal Arifin; Irdlon Sahil; Junaedi Rosyid (STAI Syaichona Moh. Cholil Bangkalan, 2022)
This study aims to determine the suitability of the curriculum 2013 with a concept of Islamic education in terms of the substance of curriculum 13 with Islamic education. This study uses a library research approach by examining the implementation of the Curriculum 2013 in the field, which is then analyzed regarding its suitability with the concept of Islamic education. The data collection method is through three events, namely observation, interviews, and documentation. Observation is the core method in this research. It is done so that researchers get valid data and then check the validity of the data through data triangulation. This study reveals that substantially there is a match between the 2013 curriculum and the concept of Islamic education, which puts the soul above physical education. Islam always emphasizes that religious education takes precedence over education about the world, as the curriculum 2013 places attitude competence above knowledge and skills by integrating science and technology and spirituality. The curriculum 2013 touches on all aspects of human life. Islam is a religion of nature, so there is no dichotomy between science and technology because Islam believes both are sourced from Allah SWT. Through revelation and reason, humans get knowledge where Allah SWT created revelation and reason